The dynamic mooring force on a wave energy Calculating the tensile force acting on the mooring structure from - BERNER WOLF, NICOLAS (My University, 2012)
This thesis tries to answer the question on how to best moor a wave energy converter that has the shape of a hose. A water wave test tank is used on a model with a scale of approximately 1:2.3 of that of the full size structure and the tensile force acting on the mooring line is then measured with a load cell. By using Froude scaling these measured forces are then used to predict the real force on an energy producing hose out in the ocean. SWAN simulated forecasted wave data provided by the Swedish Meteorological and Hydrological Institute (SMHI) is used to analyse the wave climate at five different locations along the west coast of Sweden and different potential test sites are listed in table 4.2. This thesis also suggests a mooring design that allowes the moored hose to move with the waves so that dynamic load force on the mooring line can be minimized. The static load force acting on the mooring of a 48 m hose that has a diameter of 0.5 m should range somewhere around 10-15 kN depending on wave weather and current conditions. A dynamic load force on a hose with the same dimensions should be between 12-37 kN in waves that are 1.6-5 m high. Under extreme storm conditions the dynamic response to the waves could result in forces estimated at up to 5-14 times that of the static drift force value, thus giving a dynamic force acting on the hose mentioned above of up to 50-210 kN. The force on the hose in waves that are around 5 m high should be at the lower end of this force span. Wave tank tests with 0.7 m waves and a period time of 2.6 s on a 36 m hose with a diameter of 220 mm resulted in a mooring tensile force of maximum 1000 N. Using Froude scaling, the estimated dynamic force on a 83 m long hose of 0.5 m diameter should be around 12 kN in 1.6 m high waves with a period time of 3.9 s and 37 kN in 5 m high waves with a period time of 3.9 s.
Keywords: Annan fysik; Other Physics Topics